Visceral adiposity-related dietary patterns and the risk of cardiovascular disease in Iranian adults: A population-based cohort study - Moslehi, Nazanin; Rahimi Sakak, Fatemeh; Mahdavi, Maryam; Mirmiran, Parvin; Azizi, Fereidoun (Frontiers in Nutrition, 2022)
Purpose: Diet-cardiovascular disease association (CVD) can occur through visceral obesity. However, the link between visceral adiposity-related dietary patterns (DPs) and CVD has yet to be explored. We aimed to find DPs related to visceral adiposity indicators and investigate the association between the DPs and CVD risk. Methods: We performed this prospective study on 2496 participants of the Tehran Lipid and Glucose Study (mean ± SD age: 38.1±13.3 y), who were followed from the third study examination (2005-2008; baseline) to March 2018 (mean follow-up time: 10.2 y). DPs retrieved using reduced rank regression (RRR) and partial least squares regression (PLS). Waist circumference (WC) and visceral adiposity index (VAI) were the response variables. Results: Two and three DPs were retained with RRR and PLS, respectively. The first patterns of each method were mainly characterized by adjusted-WC (RRR: 10.8%, PLS: 7.3%); none of them were associated with CVD risk. The second pattern of RRR and the third pattern of PLS were mainly explained by adjusted–VAI (RRR: 3.32, PLS: 2.1%). After adjusting for CVD risk factors, the hazard ratios (95% confidence intervals) for CVD in the second and third tertiles of the RRR-pattern 2 were 1.74 (1.14, 2.66) and 1.60 (1.03, 2.50) vs. the first tertile (p-trend: 0.040). Per one SD increase in PLS-pattern 3 score, the risk of CVD was 21% higher (4-40%). This positive association was also observed across tertiles of the pattern (p-trend: 0.025). Conclusions: For each method, we could discover a DP that was positively linked to CVD.